Dating Behaviour and Its Associated Factors among Female Adolescents in Indonesia: A School-Based Survey - Isworo, Tirta Amerta; Susanto, Tantut; Rokhmah, Dewi (Jurnal Keperawatan Soedirman, 2020)
Sexuality and reproductive health are sensitive issues for families, schools and communities to discuss with adolescents in Indonesian social, cultural and religious context. This study aims to identify dating and its associated factors in female adolescents in Indonesia. This school-based survey was conducted among 577 students who completed a self-administered questionnaire that included socio-demographic information, discussion on reproductive health with parents, teachers and peers, and physical and psychological development. The results show that 56.5% (95% CI: 51.1%–61.8%) female adolescents had dating experience. Age (OR= 1.63; 95% CI= 1.13-2.35), lack of information on development (OR= 0.39; 95% CI= 0.23-0.67), menstruation (OR= 3.07); 95% CI= 1.54-6.11), lack of discussion with teachers on the topics of puberty (OR= 2.94; 95% CI= 1.58-5.47) and dating (OR= 1.53; 95% CI= 1.03-2.28) are associated with dating behaviour. Characteristics of adolescents and discussion patterns between children and parents and teachers are also associated with dating behaviour. The results indicate that an integrated school-based sex education program that also involves parents is needed in the context of Indonesia.